The Growth and Performance of Affordable Housing Finance Lenders in India - Karmali, Nadeem M. (Washington, DC: World Bank, 2022)
Anecdotal studies have highlighted the recent rapid growth of so-called affordable housing finance companies across India. These new lenders are reported to be using a high-touch approach common to microfinance to provide mortgages to households that are newer to credit, have irregular incomes, and live in smaller urban centers. As there is no specific license type for these lenders, this paper uses detailed credit bureau data to identify which lenders could be tagged as affordable housing finance companies. Using several classification techniques, the paper then assesses their growth and performance. The results vindicate the anecdotal studies and show that this nascent sector grew at an average annual compound growth rate of 27–32 percent between 2016 and 2020. Affordable housing finance companies have been able to lend to more marginalized borrowers who are newer to credit and do so in a markedly different way than other lenders. Delinquencies at affordable housing finance companies are higher only for smaller loans, while risk-adjusted lending spreads are higher for all affordable housing finance company loan sizes. This suggests that, thus far, the approach is profitable and sustainable. Looking forward, this lending model could be useful for other countries to explore given the incipient success in India, although there are crucial capital market and institutional features that are unique to India. The paper also discusses demand-side subsidies for mortgages in India and identifies opportunities to improve the targeting of the program.